Analysis of Relationship between Pioneer Brand Status and Consumer’s Attitude toward a Brand (Case on Yamaha Automatic vs. Honda Automatic Transmission Motorcycle in Indonesia) - Hananto, Arga; Taryadi, Taryadi (ASEAN Marketing Journal, 2021)
Previous research have indicated that brand pioneership provide some advantages such as high market share barriers to entry and consumers preference as well as higher consumer attitude. This paper intends to explore the relationship between perceived brand pioneership on consumers’ brand attitude. The study focuses on two competing brands from automatic transmission motorcycle category, namely Yamaha and Honda.Based on result from 90 respondents, this study confirms the perception that Yamaha (although not the true pioneer) is perceived by the majority of respondents as the pioneering brand in the automatic transmission motorcycle. This study also found that those respondents who perceived that Yamaha is the pioneer brand tend to ascribe higher brand attitude toward Yamaha than toward Honda. Result from this study adds to the repository of studies concerning brand pioneership as well as adding to repository of knowledge about Indonesian consumer behavior.